Penyuluhan Kesehatan Mengenai Penyakit Diare dan DAGUSIBU obat pada Kader Aisyiyah Ranting Desa Potronayan, Boyolali, Jawa Tengah - Karuniawati, Hidayah; Agita Dyah Ayu Kusumaningtyas; Mufida Alfiana; Sava Salsabila Putri (Abdi Geomedisains, 2024)
Diarrhea is still a health problem in Indonesia due to high morbidity and mortality rates. In 2021, there were 29,085 cases of diarrhea experienced by the population of Boyolali District. Meanwhile, the coverage of diarrhea findings that were treated was only 5,951 cases (20,5%). Public knowledge about diarrhea disease is important to be improved to prevent diarrhea emergencies. This health counseling activity aims to increase knowledge about diarrhea and how to obtain, use, store, and dispose of drugs to members of the Aisyiyah Potronayan Village, Boyolali, Central Java.  This health counseling activity was attended by 45 participants. Before and after counseling, participants were given a pretest and post-test consisting of 15 questions. The results of the statistical analysis test showed a significant effect (p < 0.05) and an increase in the average knowledge before (67,77 ± 15,62) and after counseling (83,82 ± 8,86).